Skinny - Cooner, Donna D. (Donna Danell) (New York : Point, 2012)
After undergoing gastric-bypass surgery, a self-loathing, obese teenaged girl loses weight and makes the brave decision to start participating in high school life, including pursuing her dream of becoming a singer and finding love.
Keywords: Obesity -- Fiction; Weight control -- Fiction; Gastric bypass -- Fiction; Self-acceptance -- Fiction; Singing -- Fiction; Love -- Fiction; High schools -- Fiction; Schools -- Fiction; Young adult fiction